Effects of a high-fat diet on the lipid profile of oocytes in mice - E. Yu. Brusentsev; E. A. Chuyko; K. A. Okotrub; T. N. Igonina; I. N. Rozhkova; D. S. Ragaeva; S. V. Ranneva; V. A. Naprimerov; S. Ya. Amstislavsky (Вавиловский журнал генетики и селекции)
There are evidences that obese women exhibit a detrimental oocyte quality. However, it remains unclear how this change is associated with obesity, indirectly – or directly through a change in the content and/or composition of lipids in oocytes. The aim of this work was to study effects of a high-fat diet applied to female donor mice on the amount and qualitative composition of lipids of immature and in vivo matured oocytes. A high-fat diet caused larger body weight in female mice compared with the control (p < 0.001; 44.77±1.46 and 35.22±1.57, respectively), and increased the blood levels of cholesterol (p < 0.05; 2.06±0.10 and 1.78±0.10, respectively) and triglycerides (p < 0.05; 2.13±0.23 and 1.49±0.21, respectively). At the same time, this diet does not affect the level of unsaturation of lipids in immature (0.207±0.004 in the experiment and 0.206±0.002 in the control) and matured oocytes (0.212±0.005 in the experiment and 0.211±0.003 in the control). Total lipid content increased during in vivo maturation of mouse oocytes. The amount of lipids was greater in mature oocytes in the experimental group compared to the control (p < 0.01; 8.15±0.37 and 5.83±0.14, respectively). An increase in intracellular lipid amount during oocyte maturation was revealed both after a standard diet (p < 0.05; 4.72±0.48 and 5.83±0.14, respectively) and after a fat-rich diet (p < 0.001; 3.45±0.62 and 8.15±0.37, respectively). Thus, during in vivo oocyte maturation in mice the content of intracellular lipids enhanced, the high-fat diet aggravated this dynamics of lipid increase during in vivo maturation of oocytes.